TINDAKAN PREVENTIF DAN REPRESIF SEBAGAI UPAYA PERLINDUNGAN HUKUM TINDAK PIDANA PEMERKOSA ANAK - Imran, Muhammad Dzar; Mangesti, Yovita Arie (IBLAM LAW REVIEW, 2024)
Law Number 17 of 2016 concerning Child Protection provides special protection to children. This law regulates children's rights, parental responsibilities, child care, as well as handling cases of violence and abuse against children. This research aims to find out and explain the legal considerations taken by the judge in making a decision in the criminal case of child rape in case no. 1/Pid.Sus-Anak/2023/PN Bbs and to find out and explain the legal protection mechanisms provided to children who are victims of rape. This type of research is Normative. In this research, there are three approaches applied, namely an approach through analysis of legal regulations (statute approach), a case study (case study), and a conceptual approach (conceptual approach). Systematic Accountability in this research focuses on examining the Judge's Decision in the Child Rape case with case number No. 1/Pid.Sus-Anak/2023/PN Bbs in detail for each chapter and sub-chapter discussed, and provides supporting descriptions in the process of reviewing the Judge's Decision. Legal considerations (Ratio Decidendi) Decision No.1/Pid.Sus/Anak/ 2023/PNBBS consists of 4 elements, namely: Person or Human Element, Element of Deliberate Commitment of Deception, Element of Sexual Intercourse or Sexual Relations, Element of the person who commits it, the element that orders it to be carried out. and participate in doing it. The legal protection mechanism provided for child victims of rape is preventive: this can be done by providing information, education and understanding to the public about the applicable laws and regulations. Preventive Legal Protection Efforts by providing legal counseling, providing administrative sanctions, as well as crime prevention measures such as security patrols and security supervision. In a repressive way; Restitution and providing medical assistance/psycho-social rehabilitation assistance can be carried out in the context of restoring the victim's condition from all aspects. The restitution mechanism is regulated in Article 5 of PERMA Number 1 of 2022 concerning Procedures for Settlement of Applications and Providing Restitution and Compensation to Victims of Crime.